2019
DOI: 10.35941/jatl.1.1.2018.1507.16-23
|View full text |Cite
|
Sign up to set email alerts
|

Study of Inheritance Patterns of Morphological-Agronomic Properties on F2 Results of Local Rice Red Sikin with Ciherang Varieties

Abstract: Utilization effort sof local red rice germ plasm of East Kalimantan isconducted by cross-breeding research between local rice Sikin Merah as female elders with Ciherang varieties as male elders. This study aims to determine the pattern of inheritance of plant height, age, number of grains per panicle and panicle length, and the color of rice in the population of F2 generation plants. There search started from October 2016 until March 2017, in the tidal rice field of Sidomulyo Village, Anggana Subdistrict, Kuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In [18] study on soybean plants, the harvesting age and weight of 100 seeds followed a segregation ratio of 15:1. In the study of [4] in rice plants, the character of the number of grains per panicle follows a segregation ratio of 15:1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [18] study on soybean plants, the harvesting age and weight of 100 seeds followed a segregation ratio of 15:1. In the study of [4] in rice plants, the character of the number of grains per panicle follows a segregation ratio of 15:1.…”
Section: Resultsmentioning
confidence: 99%
“…According to, one way of increasing population diversity can be done by inducing physical mutations with gammaray irradiation. Previous research by Siahaan S., et al (2018) [4] on chili plants showed that giving gamma irradiation have the potential to produce plants with high production. Theoretically, the mutations that occur will be a random which leads to various possibilities.…”
Section: Introductionmentioning
confidence: 99%